PROFIL SGOT DAN SGPT PADA SAPI POTONG YANG TERDIAGNOSA LEPTOSPIROSIS DI KECAMATAN SEYEGAN, MOYUDAN, DAN MINGGIR KABUPATEN SLEMAN - , DANIK NOVITASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Leptospirosis is a disease which widely spread in the world. Leptospirosis is caused by pathogenic bacteria of leptospira genus and it is a zoonotic. Leptospirosis infect farm animals, wild animals, domestic animals, and humans. Leptospira attack organs such as the kidneys, liver, lungs, and reproductive organs. The aims of this research was to determine the profile of SGOT and SGPT in bovine leptospirosis in Seyegan, Moyudan, and Minggir Subdistrict Sleman Regency. A hundred and fourty seven cattles were used as a sampel. Ten milliliters blood were collected from the jugular vein using venoject. Serum was separated, for Microscopic Agglutination Test (MAT) were conducted in Bbalitvet Bogor. The MAT result is positive if agglutination between antibodies and antigens occurs in 50% dilution of 1:100 or more. If MAT was positive, liver function test was done to determine the content of Serum Glutamic Oxaloacetic Transaminase (SGOT) and Serum Glutamic Pyruvic Transaminase (SGPT). If the levels of SGOT or SGPT was found above normal, the measurement in the same sampel size would be done to use as a comparation. This test was performed at Pramita Laboratory, Yogyakarta. The results were analyzed using T-Test and descriptively. The MAT results showed that 27 from 147 samples (18,37%) were positive. A total of 7 from 26 samples (27%) showed elevated levels of SGPT. TTest results showed that there were very significant difference of SGPT levels between samples from positif MAT group (leptospirosis) and negative MAT groups (healthy). The levels of SGOT showed no increase from the normal value. From the research can be concluded that: (1) 18,37% cattles in the subdistrict Seyegan, Moyudan, Minggir Sleman Regency were diagnosed with leptospirosis. (2) A total of 27% cattles that were infected by leptospira showed elevated levels of SGPT significantly. (3) The cattles that have elevated levels of SGPT were infected by leptospira hardjo and ichterohaemorrhagiae serovar.